Protocolized management of bleeding in hospitals in The Netherlands in patients treated with direct oral anticoagulants. (2nd January 2023) - Mitrovic, Darko; Stapel, Lilian; Veeger, Nic; Lameijer, Heleen; Meijer, Karina; van Roon, Eric
Abstract: Objective: To investigate and describe the protocolized treatment of DOAC-related bleeds in all Dutch hospitals. Methods: From August to December 2020 a nationwide survey among all 70 hospitals in the Netherlands was conducted on their protocols for management of bleeding in patients treated with direct oral anticoagulants (DOACs, i.e. apixaban, edoxaban, rivaroxaban and dabigatran). The protocols were assessed the following characteristics: bleeding definitions (mild, moderate and severe bleed), diagnostic parameters (hemoglobin [Hb], loss of blood, surgical procedure needed, etc), first and second choice of treatment, effectiveness criteria and the level of evidence/references upon which protocols were based. Results: All 70 hospitals responded (100%). We received 69 protocols in total, 6 of which were identical because hospitals worked together. In 35 (50%) of the protocols a definition of minor, moderate or severe bleeds was described. Diagnostic parameters for bleeds were present in 2%, 41% and 47% of protocols for a mild, moderate and severe bleed. While the first choice treatment for severe bleeding under dabigatran was idarucizumab in 96% of protocols, considerably more therapeutic options (mostly different prothrombin complex concentrate (PCC) doses) are described for Xa inhibitors. When considering criteria for effectiveness more than 90% of protocols did not have a clear description. Conclusion: This study provides an overview of the current state of protocols for management of DOAC-related bleeding in The Netherlands. Protocols vary in the content of information provided and often do not include information, especially for diagnostic criteria and criteria for establishing the effectiveness of the intervention. The results of this study can assist in improving and harmonizing the protocols.